Kajian Konsumsi Bbm Pengguna Kendaraan Pribadi Roda Empat Di Jabodetabek - Zulfikri, Zulfikri; Maimunah, Siti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Economic growth contributes to the high demand for public consumption, including thepurchase of vehicles which resulted in an increase in the consumption of fuel (BBM). Fuelconsumption at the four-wheeled vehicles (R4) is highly influenced by various factors thatdetermine the level of efficiency of use. Appropriate and accurate information aboutconsumption and fuel efficiency is needed to determine the various efforts related to theenergy saving, particularly for private cars that dominate the traffic in urban areas. Thestudy was done by quantitative descriptive using data and information obtained directlyfrom the user's private cars in jabodetabek area (Jakarta, Bogar, Depok, Tangerang andBekasi). R4 vehicle types consume the most fuel of premium compared with other types offuels (diesel or pertamax).